One‐year intranasal application of growth hormone releasing peptide‐2 improves body weight and hypoglycemia in a severely emaciated anorexia nervosa patient. Issue 3 (27th April 2015) - Haruta, Izumi; Fuku, Yuki; Kinoshita, Kazuhisa; Yoneda, Koichi; Morinaga, Akinori; Amitani, Marie; Amitani, Haruka; Asakawa, Akihiro; Sugawara, Hideki; Takeda, Yasuo; Bowers, Cyril Y.; Inui, Akio
Abstract: Background: In Japan, growth hormone releasing peptide‐2 (GHRP‐2) is clinically used as a diagnostic agent for growth hormone secretion deficiency, but the therapeutic application of GHRP‐2 has not been studied in anorexia nervosa. GHRP‐2 reportedly exhibits agonistic action for ghrelin receptor and increases food intake. Methods: We administered GHRP‐2 to a patient with a 20‐year history of anorexia nervosa to determine whether GHRP‐2 treatment increases food intake and body weight. GHRP‐2 was administered before every meal by an intranasal approach for 1 year. Results: Although the patient reported a decreased fear of eating and decreased desire to be thin by our previous treatment, she was unable to increase food intake or body weight because of digestive tract dysfunction. Vomiting after meals caused by delayed gastric emptying and incurable constipation were prolonged, and sub‐ileus and hypoglycemia were observed. GHRP‐2 increased the feeling of hunger and food intake, decreased early satiety and improved hypoglycemia. The patient's body weight gradually increased by 6.7 kg (from 21.1 kg to 27.8 kg) in 14 months after starting GHRP‐2 administration. The fatigability and muscle strength improved, and the physical and mental activities were also increased. No obvious side effects were observed after long‐term intranasal administration of GHRP‐2. Conclusions: Patients with a long‐term history of eating disorder occasionally recover from the psychological problems such as fear for obesity but remain emaciated. We believe that ghrelin agonists such as GHRP‐2 may be promising agents for the effective treatments of severe anorexia nervosa in a chronic condition.